(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
The study aims to research the correlation between unemployment and inflation in Sweden between March 2020 - November 2021 to provide further insight into the validity of the Phillips curve. Previous research has found a contradictive relationship between unemployment and inflation. In addition, shifting market trends with lower globalization and higher inflation provide attention to evaluate the Philips curve. The focus is on Sweden because it is a small country with a high level of dependency on trade and technology. For that purpose, an econometric analysis has been applied to Swedish unemployment and inflation data between March 2020 - November 2021 to generate the correlation and examine the validity of the Phillips curve. The results indicate a weak linear relationship, suggesting that other variables than inflation have a more significant effect on unemployment than inflation. A possible explanation might be the inflation target that the Swedish Central Bank (Riksbanken) implemented in 1993, which contributed to a stable inflation level until 2021